Expanded Access Use of Rezafungin for Salvage Therapy of Invasive Candida glabrata Infection: A Case Report. (28th August 2021) - Adeel, Alina; Qu, Ming D; Siddiqui, Efaza; Levitz, Stuart M; Ellison, Richard T
Abstract: Rezafungin is a semisynthetic, long-acting echinocandin with broad-spectrum activity against many Candida species and Aspergillus species, including a subset of drug-resistant strains. It is currently in phase III trials and was found to be safe and effective for the treatment of candidemia and/or invasive Candida infections in a phase II trial. However, there are no long-term safety or efficacy data. We report on the successful ongoing compassionate use of rezafungin obtained through expanded access for over 1 year in a patient with a multidrug-resistant Candida glabrata mediastinal infection from a vascular graft infection and retained foreign material.